Development of acoustic maps in Heredia, Alajuela and Belén counties, as indicators of noise pollution. - Bermúdez-Hidalgo, Ligia (2019)
The present study corresponds to the conformation of acoustic maps based on the collection of  noise data in the urban centers of Heredia, Alajuela and Belén, in Costa Rica donwtown. Therefore, a sampling was carried out using sites of complaint for noise pollution in Alajuela and Belén, while in Heredia the vertices of each quadrants in Central District were used as a sampling site. The most important result obtained in this study is related to the identification of mostly sites withnoise levels that exceed the permissible limits established in the Regulation that can be observed graphically in the acoustic maps. This leads to the following conclusion the acoustic maps represent a fundamental tool for the noise control and to plan the mitigation strategies and confinement of noise pollution areas.